Management Skills and Styles of School Principals during the COVID-19 Pandemic - Khazni Taun; Mª Luisa Zagalaz-Sánchez; Ramón Chacón-Cuberos (MDPI AG, 2022)
The present study investigated a significant issue among a population with unique characteristics. This research and discussion centered on the challenges of running a school during the COVID-19 pandemic. The central question in this study was, how do school principals perceive their abilities and the skills required to run schools during the pandemic? In addition, this study aimed to assess the awareness of the teachers that were subordinate to these same school principals and the impact of their leadership style. The current study involved 151 teachers and 18 school principals from 18 governmental Bedouin schools in Israel. Structured questionnaires were used to collect data and measure the research variables. To analyze the data, indices and statistical tests were applied using SPSS software. The main research findings indicated that the teachers perceived the leadership styles of their school principals as a formative and rewarding part of their personality and not as an evasive style. The principals reported a high level of availability and accessibility and appropriate communication levels with all of the relevant parties. Moreover, the principals reported their level of decision-making ability as high, their judgment calls as sound, and their organizational planning skills and knowledge-development abilities as excellent. Additionally, cultivating the organizational structure was a priority for the principals; they believed that they could develop a comfortable and supportive organizational atmosphere and that this was the core of their work. The school principals perceived themselves as having the requisite skills, including a high level of ability and efficient team management. Self-confidence and a high level of competence helped the school principals cope with the challenges of the COVID-19 pandemic and traverse them safely.